On Besov regularity of solutions to nonlinear elliptic partial differential equations. (March 2020) - Dahlke, Stephan; Hansen, Markus; Schneider, Cornelia; Sickel, Winfried
Abstract: In this paper, we study the regularity of the solutions of some nonlinear elliptic equations in Kondratiev spaces on certain domains of polyhedral type. General embedding theorems between Kondratiev spaces and Besov spaces will allow to avoid drawbacks to the standard Sobolev regularity theory for those nonsmooth domains. This will give us the opportunity to derive optimal rates for certain nonlinear approximation schemes.